Applied history, applied economics, and economic history - Christopher L. Colvin; Paul Winfree (Queen's University Centre for Economic History (QUCEH), 2019)
As a new field of academic enquiry, applied history has a unique opportunity to learn lessons from other applied fields. In this essay, we set out how we think applied historians can learn from the mistakes of applied economists and economic policymakers in their use, and abuse, of economic theory and economic history. What we call the New Applied History has the potential to improve the way policymaking is conducted. But only if its practitioners understand the power, and limitations, of theory. We apply our ideas to the case of budgetary policymaking in the United States.
Keywords: B15; B22; E12; E63; N12; N41; 330; applied history; budgetary policy